Análise da estrutura genética populacional da piraúna (cephalopholis fulva: serranidae) ao longo da costa e ilhas oceânicas brasileiras - Souza, Allyson Santos de (2011)
Brazil has about 8,500 km of coastline and on this scale, fishing is a historically important source of animal protein for human consumption. The national fishing background shows a growth of marine fishery production until 1985 and within this period it was recorded a steady decline. From the year 2003 fishing statistics aim to some "recovery" of the total fisheries production, which probably is related to a change in industry practice. The target of commercial fishing became smaller species with low commercial value, but very abundants. The coney, Cephalopholis fulva (Serranidae), is one of these species that have been suffering a greater fishing pressure in recent years. In order to provide data about the current situation of the genetic diversity of these populations, several molecular markers have been being used for this purpose. The prior knowledge of genetic variability is crucial for management and biodiversity conservation. To this end, the control region sequences (dloop) of mtDNA from Cephalopholis fulva (Serranidae) from five geographical points of the coast of Brazil (Ceará, Rio Grande do Norte, Bahia and Espírito Santo) and the Archipelago of Fernando de Noronha (FN) were sequenced and their genetic diversity analyzed. The FST values were very low (0.0246 to 0.000), indicating high gene flow between the sampled spots. The indices h and indicate a secondary contact between previously allopatric lineages differentiated or large and stable populations with long evolutionary history. Tests of Tajima and Fu showed expansion for all populations. In contrast, the mismatch distribution and SSD indicated expansion just for coastal populations. Unlike other species of the Atlantic which have been deeply affected by events on later Pleistocene, the population-genetic patterns of C. fulva may be related to recent events occurred approximately 130,000 years ago. Moreover, the data presented by geographical samples of the specie C. fulva showed high genetic diversity, also indicating the absence of deleterious effects of over-exploitation on this specie, as well as evidence of complete panmixia between all sampled populations